Pyrolytic Conversion of Waste Hemp: Kinetics, Product Characterization, and Boosted Regression Tree Modeling - Ali, Imtiaz; Seyfeli, Rukan Can; Tahir, Mudassir Hussain; Ceylan, Selim (Elsevier, 2023)
This study investigated the pyrolysis of hemp residue using kinetic analysis. The thermal degradation of hemp residue occurred in three temperature ranges, and the activation energy (Ea) varied between 147.5 kJ/mol and 299.2 kJ/mol depending on the model-free method used. Combined kinetics, statistical approach, was used to calculate the kinetic triplets including the reaction mechanism and pre-exponential factor besides Ea. Boosted regression trees (BRT), machine learning approach, was used to predict the Ea during the course of conversion at different heating rates. Bio-oil extracted from hemp residues at different temperatures was examined. The oil contained valuable compounds, including phenols, esters, ethers, aromatics, hydrocarbons, organic acids, furans, alkanes, and ketones. The production of hydrocarbons was found to increase at elevated temperatures, indicating their bioenergy potential. However, acids and esters formation decreased at higher temperatures, while aldehydes were produced by the breakdown of a sugar ring. The study provides insights into the potential of hemp residue to be used in the production of value-added products.
Ali, Imtiaz/0000-0001-6303-6164; Seyfeli̇, Rukan Can/0000-0002-4432-0490;
Keywords: Hemp Residue; Pyrolysis; Isoconversional Kinetics; Combined Kinetics; Boosted Regression Tree; Py/GC-MS